Inequity in nature’s contributions to people in Ōtautahi/ Christchurch: A low-density post-earthquake city - Daniel Richards; Maksym Polyakov; Angela J. Brandt; Jo Cavanagh; Gradon Diprose; Grace Milner; John V. Ramana; Robyn Simcock (Urban Forestry & Urban Greening, 2023)

Measuring the impact of food rescue: A social return on investment analysis - Grace Clare; Gradon Diprose; Louise Lee; Phil Bremer; Sheila Skeaff; Miranda Mirosa (Food Policy, 2023)

Methodological sensitivities for co-producing knowledge through enduring trustful partnerships - Alison Greenaway; Holden Hohaia; Erena Le Heron; Richard Le Heron; Andrea Grant; Gradon Diprose; Nicholas Kirk; Will Allen (Sustainability Science, 2022)
Indigenous ways of caring for the environment have long been marginalised through research methodologies that are blind to a range of ways of knowing the world. Co-production of knowledge across Indigenous knowledge systems and Western scientific approaches is receiving attention both internationally and within the science system in Aotearoa New Zealand. Addressing power asymmetries as part of the co-production process is also slowly gaining recognition. Those involved in knowledge co-production initiatives must support learning about different world views, ways of knowing and accounting for the environment, while also enabling learning of the many biases and assumptions built into methodologies. This deliberation is needed, so non-Indigenous researchers can form enduring trustworthy partnerships and contribute to co-production initiatives. Presented here are insights shared by a cohort of environment research practitioners who have been deliberating on co-production occurring across knowledge systems in Aotearoa New Zealand. Originating from analysis of interviews undertaken about relationships recreational groups have with Te Urewera (forested hill country in the North Island of Aotearoa New Zealand), this paper depicts a layered reflection on how non-Māori (primarily but not exclusively) across Aotearoa New Zealand are learning to be manuhiri (those being welcomed on arrival to a place by the Indigenous people of that place). As a contribution to this collective learning, a set of methodological sensitivities are proposed as support for research amidst changing relationships with places. Doing so we aim to contribute to reflexive and decolonising encounters with Indigenous approaches to environmental care.